Influences of Hardened Aluminium HMMC on Tribological, Flexural and Impact Strength of Wheel Rim Element with Prognostications - S. Kamatchisankaran; A. Bovas Herbert Bejaxhin; K. Ramkumar; N. Ramanan (Archives of Metallurgy and Materials)
The primary goal of this research is to develop hybrid non-ferrous material composites with high flexural and impact strengths by testing the mechanical, thermal, and corrosion properties of AA 6061 wheel rims with various silicon carbide (SiC) and zirconium sulphide (ZrSO4) compositions. This produces an alloy with high strength and perceptible hardenability that is used in a variety of marine space industries. Because of its exceptional strength-to-density ratio, it is a highly sought-after metal matrix composite in the automobile industry. This innovative composite material offers lower weight and higher impact strength when compared to the current wheel rim alloy. Designs of experiments based recommendations and results of simulations in order to prolong the life of the wheel rim.